Design and Simulation of Reduced Switch 31-Level Multilevel Inverter Topology for PV Application - Abdulhasan, Abdulhasan F.; Jaber, Fatimah F.; Kheerallah, Yousif Abdulwahab (Iraqi Journal for Electrical and Electronic Engineering, 2024)
This paper presents a design of a low cost, low loss 31-level multilevel inverter (MLI) topology with a reduce the number of switches and power electronic devices. The increase in the levels of MLI leads to limiting the THD to the desired value. The 31-level output voltage is created using four PV sources with a specific ratio. The SPWM is used to control the gating signals for the switches of MLI. The PV system is integrated into the MLI using a boost converter to maximize the power capacity of the solar cells and the Incremental Conductance (IC) algorithm is employed for maximum power point tracking (MPPT) of the PV system. Simulation results of 31-level MLI indicate the THD of voltage and current waveforms are 3.73% within an acceptable range of IEEE standards.